An adapted suction technique to aid removal of ruptured silicone implants. (June 2019) - Pizzonia, Giuseppe; Sasso, Andrea; Musumarra, Gaetano
Abstract: Implant rupture is a common complication of breast implant surgery. Removal of silicone gel after breast implant rupture can be difficult and time-consuming. In the medical literature, a few other methods attempt to solve this challenge. We propose a simple and efficient technique to maximize its removal by suction. This method bypasses the problem, given the disadvantages of silicone's high viscosity. Moreover, the necessary equipment is inexpensive and readily available in any operating room.